INDONESIAN ISLAMIC EDUCATION: TOWARDS SCIENCE DEVELOPMENT - Handoko Ja'far (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
Education as the root of civilization has an important role in preparing human resources toward the effort of developing sciences. Nowadays, Moslem in the world are divided into two attitudes: resisting and refusing the development of sciences. Both of the attitudes are needed to bridge wisely. It meant no one is burdened in facing modern sciences by the ways of appreciating the modern sciences, applying them appropriately and learning from the history of the development of knowledge in the glory age of Islam. This article tried to confirm that science as a result of education, is not only the representation of civilization but also the demonstration of the high value of civilization. In Indonesia, the idea to reconstruct the model of Islamic education is getting stronger in accordance with the development of modern education. In this context, the clasical knowledge as heritance needed to be transformed into the modern one. Transformation is something unavoidable by the institutions of Islamic education.